2022
DOI: 10.1371/journal.pone.0279571
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and its associated factors among people living in post-war Districts of Northern Ethiopia: A cross-sectional study

Abstract: Background War and conflict environments result in long-term physical and psychological consequences. Sexual violence, displacement, malnutrition, death, illness, injury, torture, and disability are some of the physical effects, whereas stress, depression, aggressive behaviors, and anxiety are some of the emotional complications of war. Hence, evidence-based interventions are required particularly to monitor mental health disorders. Thus, we aimed to investigate the prevalence of perceived stress and its assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…On the other hand, the results of this study are lower than the findings from Ethiopia, in Tigray (82.1%) [17], in conflict-affected areas during the COVID-19 era, (59.8%) [18], and another study in north Shewa, (76.1%) [19], the Democratic Republic of Congo 57% among female refugees [48], and in Juba, southern Sudan (58.73%) [12]. The possible explanations for the differences might be the diverse sociocultural background of the study populations.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the results of this study are lower than the findings from Ethiopia, in Tigray (82.1%) [17], in conflict-affected areas during the COVID-19 era, (59.8%) [18], and another study in north Shewa, (76.1%) [19], the Democratic Republic of Congo 57% among female refugees [48], and in Juba, southern Sudan (58.73%) [12]. The possible explanations for the differences might be the diverse sociocultural background of the study populations.…”
Section: Discussioncontrasting
confidence: 91%
“…Previous research works revealed that the prevalence of mental health problems were high in conflict-affected areas. For instance, depression 51.6-82,1% [16,17], mental distress 59.4% [18] and perceived stress 76.1% [19], and post-traumatic stress disorder ranges 34.5 − 59.8% [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%